A compact dual‐band crossover using coplanar‐waveguide‐fed dual‐mode ring resonators. Issue 1 (14th November 2018) - Feng, Wenjie; Shen, Xiaoxiang; Che, Wenquan
Abstract: In this article, a compact dual‐band crossover using dual‐mode ring resonators by Coplanar‐Waveguide (CPW)‐Fed scheme is proposed. It contains 2 homocentric square ring resonators on the top layer to obtain the dual‐band responses. CPW feeding lines and open stubs are placed on the bottom layer to feed the ring resonators and adjust coupled strength. The center frequencies and bandwidths for each passband can be individually controlled easily. To prove the design concept, a compact dual‐band crossover operated at 1.57 and 2.45 GHz is designed and fabricated. The measured results show good agreement with the simulation ones results a wide frequency range.